2005
DOI: 10.31274/ans_air-180814-1370
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variation to Healthfulness of Beef

Abstract: and Implications The objective was to determine the natural variability in beef fatty acid composition and to identify single nucleotide polymorphisms (SNPs) in the stearoyl-CoA desaturase (SCD) gene to test the association of SNPs with fatty acid composition. We have used common gas chromatographic techniques to determine the fatty acid composition of phospholipids and triacylglycerols (TAGs) extracted from beef muscle (longissimus dorsi) from 800 sire-identified cattle originating from Iowa State University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They showed that, in Japanese Black cattle, allele C was more frequently associated with a higher content of MUFA in carcasses, and suggested that genotyping for this region would be a useful tool for selection of favorable beef carcasses. Zhang (2005) tested the effect of the Val/Ala variant on the individual fatty acid composition of fat extracted from beef muscle (longissimus dorsi) of 172 bulls. They found that the Val allele was more frequent (0.83) in the analyzed cattle, but agreed with Taniguchi et al (2004) in that heterozygous Val/Ala (C/T) animals had higher C16:1/C16:0 in intramuscular fat than did homozygous Val (TT) animals.…”
mentioning
confidence: 99%
“…They showed that, in Japanese Black cattle, allele C was more frequently associated with a higher content of MUFA in carcasses, and suggested that genotyping for this region would be a useful tool for selection of favorable beef carcasses. Zhang (2005) tested the effect of the Val/Ala variant on the individual fatty acid composition of fat extracted from beef muscle (longissimus dorsi) of 172 bulls. They found that the Val allele was more frequent (0.83) in the analyzed cattle, but agreed with Taniguchi et al (2004) in that heterozygous Val/Ala (C/T) animals had higher C16:1/C16:0 in intramuscular fat than did homozygous Val (TT) animals.…”
mentioning
confidence: 99%